Dural sinus thrombosis: verification with spin-echo techniques. - Sze, G; Simmons, B; Krol, G; Walker, R; Zimmerman, R D; Deck, M D (American Journal of Neuroradiology, 1988)
Although MR imaging is being used increasingly to detect dural sinus thrombosis, accurate evaluation of images has often been hindered by the presence of artifacts, especially flow-related enhancement, that may simulate intraluminal clot. We tried an approach with spin-echo techniques to eliminate flow-induced artifacts and, thus, facilitate the diagnosis of dural sinus thrombosis. In this investigation, a nonselective single-section spin-echo verification method was used as a prototype of this approach. Both patients and an experimental flow phantom were used to test the validity of this concept. Clinically, thrombosis was seen to persist as isointense or highly intense signal in the vascular lumina with the specialized sequence, while flow-related artifacts were replaced by hypointense signal, but not by signal void. These same changes were examined both quantitatively and qualitatively in the flow phantom by using varying velocities of flow. Although our clinical investigation concerns suspected dural sinus thrombosis, the principles of these specialized spin-echo techniques can be applied successfully throughout the head to eliminate certain flow-related artifacts.